2019
DOI: 10.1039/c9bm00044e
|View full text |Cite
|
Sign up to set email alerts
|

Short, symmetric-helical peptides have narrow-spectrum activity with low resistance potential and high selectivity

Abstract: A narrow-spectrum antimicrobial peptide was obtained via database-filtering technology and symmetric-structure; the peptide disturbed bacterial membrane and reduced the cytokine levels in serum in the mouse model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 59 publications
4
61
0
Order By: Relevance
“…In this study, two symmetric heptad repeat sequences were connected by a short loop, and the sequence was designed as XXRXXRRzzRRXXRXX-NH 2 , where X represents Phe (F), Ile (I), and Leu (L), while zz represents Gly-Gly (GG) or d-Pro-Gly (pG). The net charge was +6 and the hydrophobicity was 40%-60%, which is consistent with the statistical information on natural AMPs [2,18]. Hydrophobic amino acids F, I, and L were used to damage microbial cell membranes [19].…”
Section: Introductionsupporting
confidence: 74%
“…In this study, two symmetric heptad repeat sequences were connected by a short loop, and the sequence was designed as XXRXXRRzzRRXXRXX-NH 2 , where X represents Phe (F), Ile (I), and Leu (L), while zz represents Gly-Gly (GG) or d-Pro-Gly (pG). The net charge was +6 and the hydrophobicity was 40%-60%, which is consistent with the statistical information on natural AMPs [2,18]. Hydrophobic amino acids F, I, and L were used to damage microbial cell membranes [19].…”
Section: Introductionsupporting
confidence: 74%
“…Following this Trp motif, a positive-charged amino acid arginine (Arg), which causes toroidal pore defects in the anionic membrane and positively influences electrostatic interactions between peptides and the negatively charged bacterial membrane surface (Chou et al, 2016), was added to obtain amphipathic sequences. Our research indicated a vital role of the hydrophilic amino acid to adjust the antibacterial spectrum but its exact effect was not distinguished (Chou et al, 2019). Finally, the resulting primary peptide structure simplified as RRWyWWWyWRR, where y represents an uncharged hydrophilic amino acid (Schema 1) was proposed as a probiotic-neutral sequence.…”
Section: Introductionmentioning
confidence: 89%
“…The mechanism of the designed peptides was measured by fluorescence spectroscopy and electron microscopy as shown before. The fluorescent dyes disc 3 -5 , β-galactosidase, calcein and BC were used to determine cytoplasmic membrane depolarization and the binding affinities of the peptides to LPS and LTA (Wen et al, 2013;Chou et al, 2019). Briefly, for depolarization, 0.4 µM disc 3 -5 was added to the bacteria, which were washed and diluted into an OD600 of 0.05 with 5 mM HEPES buffers (containing 20 mM glucose and 0.1 KCl); for inner membrane permeability, bacteria incubated in LB containing 2% lactose were washed and diluted to an OD600 of 0.05 with 10 mM PBS (pH 7.4) containing 1.5 mM ONPG; for LPS or LTA binding, LPS/LTA and BC were mixed in Tris buffer (50 mM, pH 7.4) with a final concentration of 50 and 5 µg/ml, respectively.…”
Section: Antimicrobial Mechanism Measurementmentioning
confidence: 99%
See 2 more Smart Citations